An Overview of Bone Cement Compositions used in Vertebroplasty and Their Viability in Clinical Settings (International Journal of Engineering Materials and Manufacture, 2024)
Vertebroplasty is a minimally invasive surgical procedure wherein a particular composition of bone cement is injected into a fractured vertebra in an attempt to restore joint mobility and reduce perceived pain. It is especially common in the treatment of osteoporotic vertebral compression fractures, most typically experienced by older women. The formulation of this bone cement takes on many forms, the most common being the group of cements known as polymethyl methacrylate acrylic bone cements. The different varieties of acrylic bone cements are investigated and compared, in addition to new potential rival materials being developed to rival the dominance of acrylic bone cements in the vertebroplasty bone cement industry. Factors such as biomechanical strength, handling, osteoconductivity/inductivity, biodegradability, additive delivery, and porosity are considered. While the main drawbacks of acrylic bone cements (significant biomechanical mismatch with vertebrae and lack of biodegradability and osteoconductivity) present opportunities for new solutions to enter the market to compete, the industry standard in vertebroplasty remains the most widely applicable, and thus wisest, cement choice for the procedure.Keywords: Vertebroplasty, Minimally Invasive Surgery, Biodegradability, Bone Cement